2020
DOI: 10.21203/rs.3.rs-31362/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial Predominance and Antimicrobial Resistance in a Tertiary Hospital: A Six-year Retrospective study from Outpatients and Patients Visiting the Emergency Department

Abstract: Objective: To assessing the characteristics of of microbial species and the antimicrobial resistance in a Tertiary Hospital with 49 outpatient clinics and emergency department in Northwestern China, of six years. Methods: A retrospective study was conducted using HIS database of a tertiary hospital between the full-year period of 2013 and 2018. Antimicrobial susceptibility tests were conducted by automated systems and/or the Kary-Bauer disc diffusion method. Data were analyzed using the WHONET 5.6 software. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…To evaluate the predominant bacterial in blood culture and their antimicrobial susceptibility patterns 180 patient has been selected according to inclusion and exclusion criteria. Blood culture positivity has been seen in 12 (7%) cases which is quite similar to Gohel et al (9.2%)12 and Mehta et al (9.94%)13 and Wang et al (12.9%) 14 . The participants who were above 15 years age were predominant 91(51%) than participants were below 15 years age 87(49%).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…To evaluate the predominant bacterial in blood culture and their antimicrobial susceptibility patterns 180 patient has been selected according to inclusion and exclusion criteria. Blood culture positivity has been seen in 12 (7%) cases which is quite similar to Gohel et al (9.2%)12 and Mehta et al (9.94%)13 and Wang et al (12.9%) 14 . The participants who were above 15 years age were predominant 91(51%) than participants were below 15 years age 87(49%).…”
Section: Discussionsupporting
confidence: 82%
“…The study of Gohel et al has been reported that the positive blood cultures were obtained in 9.2% of cases of which Gram positive bacteria accounted for 58.3% of cases with staph aureus predominance 17 . A study has been conducted among blood stream infection patients has been recorded that about 44.6% isolates are Gram-negative bacilli and frequently identified species were Escherichia coli, Klebsiella pneumonia and Pseudomonas 18 . Prevalence of gram negative bacterial etiology of septicemia in children has been recorded by several other authors 19,20 .…”
Section: Discussionmentioning
confidence: 99%